Middle School Mathematics Lessons to Explore, Understand, and Respond to Social Injustice - Conway IV, Basil Manley; Conway IV, Basil Manley; Deen, Lateefah Id; Raygoza, Mary C.; Ruiz, Amanda; Staley, John W.; Thanheiser, Eva (Thousand Oaks : Corwin, 2023)
Written for teachers committed to developing equitable and empowering teaching practices through the lens of mathematics content and practice standards as well as social justice standards, this book will help connect middle school mathematics content to young adolescences' daily lives, strengthen their understanding of mathematics, and support them to see their agency as active agents of change and responsible leaders.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Mathematics; Secondary Math